1985
DOI: 10.3171/jns.1985.62.2.0169
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of adrenal medullary tissue to striatum in parkinsonism

Abstract: Autologous adrenal medullary tissue was transplanted to the striatum in two patients with severe parkinsonism. The aim was to provide the striatum with a new cellular source of catecholamines. Some rewarding effects were registered. This is the first time that such tissue has been transplanted in the human brain. The results merit further clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
150
0
3

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(153 citation statements)
references
References 25 publications
0
150
0
3
Order By: Relevance
“…Prior to and conings of the primate caudate and putamen preceding earliest movement-related muscle activity show electrical comitant with these primate studies, a number of clinical trials using adrenal medulla grafts were attempted; howactivity in the caudate and putamen (45), suggesting that both may be critical targets for neural replacement. ever, these resulted in transient behavioral benefits and high morbidity (7,9,38,51,64,67,90). Postmortem studies Not only did these double-blinded trials fail to demonstrate uniform functional benefit, the induction of a confirmed the nonhuman primate experiments; graft survival was poor and the degenerating grafts induced a serious new side effect called graft-induced dyskinesias was noted.…”
Section: Genetic Modelsmentioning
confidence: 99%
“…Prior to and conings of the primate caudate and putamen preceding earliest movement-related muscle activity show electrical comitant with these primate studies, a number of clinical trials using adrenal medulla grafts were attempted; howactivity in the caudate and putamen (45), suggesting that both may be critical targets for neural replacement. ever, these resulted in transient behavioral benefits and high morbidity (7,9,38,51,64,67,90). Postmortem studies Not only did these double-blinded trials fail to demonstrate uniform functional benefit, the induction of a confirmed the nonhuman primate experiments; graft survival was poor and the degenerating grafts induced a serious new side effect called graft-induced dyskinesias was noted.…”
Section: Genetic Modelsmentioning
confidence: 99%
“…By the 1980s, groups in Sweden and Mexico were reporting transplantation of autologous adrenal tissue into the brains of patients with PD via both open craniotomy and stereotactic approaches. 39,40 Although the thalamus had been the preferred target for patients with PD prior to the introduction of L-dopa, 17 Laitinen et al 41,42 popularized pallidotomy as the principal procedure for patients with advanced, medically refractory PD in the early 1990s. There were several reasons for this change: 1) the patients may have had more advanced disease in the 1990s than in the 1950s and 1960s since they had failed L-dopa, 2) DeLong et al's 43 nonhuman primate model pointed to a more important role in the circuitry of PD for the globus pallildus pars interna (GPi) than the ventrointermedialis nucleus (Vim) of the thalamus, and 3) better outcome measures may have detected differences that were initially missed in the 1950s and 1960s.…”
Section: The Resurgence Of Surgical Treatment For Movement Disordersmentioning
confidence: 99%
“…In pioneering work performed by Olson, Seiger and Backlund and their co-workers [3,4], autologous adrenal medulla cells were implanted into striatum of four PD patients to provide a local catecholamine source but the beneficial effects were minimal. Similarly, after an initial hype with open microsurgery and pieces of adrenal medulla tissue placed in the caudate nucleus [5], this method was abandoned because of lack of efficacy and adverse effects.…”
Section: Introductionmentioning
confidence: 99%